Mary Turner and the memory of lynching - Armstrong, Julie Buckner (Univ. of Georgia Press, 2011)
Birth and nation: Mary Turner and the discourse of lynching -- Silence, voice, and motherhood: constructing lynching as a Black woman's issue -- Brutal facts and split-gut words: constructing lynching as a national trauma -- Contemporary confrontations: recovering the memory of Mary Turner -- Conclusion: marking a collective past